PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SUSTAINABILITY REPORTING - Nutriastuti Nutriastuti; Dea Annisa (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
This study aimed to get empirical evidence about the influence of Corporate Social Responsibility Disclosure and Quality Audit to Corporate Sustainability Reporting. Corporate Social Responsibility Disclosure was proxied by CSRDI (Corporate social responsibility disclosure index) based on indicators GRI 2016. Audit quality was proxied by big-four accounting firm or non big-four and measured by a dummy variable. The level of Corporate Sustainability Reporting disclosure measured through Sustainability Report Disclosure Index (SRDI) is expressed by comparing the number of disclosures by the company with a number of standar disclosure of the Global Reporting Initiative (GRI) 2016 index. The type of research is an associative quantitative research with the determination of samples testing purposive sampling method, of obtaining samples based on certain criteria. The data used is secondary data collected through companies listed on The Indonesia Stock Exchange. Hypothesis testing is done by technique, classic assumption test analysis and multiple linear regression test analysis used in this study to answer the main problem of research. The data collecied, then processed and analyzed using the program SPSS 25.0 for windows. The result of this study indicate that Corporate Social Responsibility has a significant positive effect on Corporate Sustainability Reporting. Audit Quality has no significant positive effect on Corporate Sustainability Reporting. SIZE has no significant positive effect on Corporate Sustainability Reporting. Simultaneous hypothesis testing shows that Corporate Social Responsibility, Audit Quality and SIZE together have a significant positive effect on Corporate Sustainability Reporting.